The Valuation Effects of Private Placements of Public Corporations' Common Stock - W. R. McDaniel; William R. McDaniel (Journal of Small Business Finance, 1992)
Outside shareholders should benefit when the firm issues common stock through a private placement. Our propositions are (1) that the private issue of common equity creates a value-maximizing insider that has the incentive and ability to monitor and discipline, and thereby reduce agency costs and (2) investors can reduce uncertainty about the value of thinly traded stock by observing the share price negotiated by the well-informed buyer. Both of these benefits are especially applicable to small firms. Our empirical evidence supports hypotheses based on these propositions.
Keywords: G12; G32; 650; Valuation; Stock; Equity; Private Placements